PENELANTARAN EKONOMI DALAM KELUARGA (TINJAUAN FIQH DAN UU PKDRT) - Khairani Khairani (Pusat Studi Wanita UIN Ar-Raniry, 2017)
Nowadays, ignoring family often results separation inside the family, especially after the avail- ability of Law Domestic Violence (Domestic Violence Act). However, Islamic judiciance (Fiqh) looks differently toward this case so that it is necessary to study fiqh muqarran. Furthermore, this argument needs to be related to the phenomenon that occurs due to the Domestic Violence Act.